Mechanistic insights into excitonic and electrostatic stimulation of cells by photovoltaic substrates/nanocrystals and through light polarization modulation - Mohammad Mohammadiaria; Daniel L. Rathbun; Moses Kamita; Shashi Bhushan Srivastava (PLoS ONE, 2025)
Photoelectrical stimulation of cells and neural modulation via the separation of photo-induced electrical charges in photocapacitor structures have proven effective and biocompatible for therapeutic applications, such as retinal prostheses. Recent advances in photovoltaic materials and device architectures, particularly the use of pixelated photoelectrodes, have enabled high-resolution modulation of neuronal transmembrane potentials. Upon illumination, photo-induced dipoles and excitons in semiconductor layers generate localized electric fields that interact with the cell membrane to trigger stimulation. Polarization-modulated light dynamically alters the orientation of these dipoles, modulating field orientation and enhancing light–matter coupling at the membrane interface. This effect is especially pronounced in anisotropic media or aqueous environments, where polarization control enables deeper, more focused light penetration. Our framework combines (1) a photocapacitive mechanism that displaces charge across the cell membrane through excitonic microdomain redistribution in the photovoltaic hybrid and (2) an electrostatic force from photo-induced dipoles near the cell. These effects are embedded in an equivalent-circuit model that links optical inputs (intensity and polarization) to the device’s open-circuit voltage (V OC ) and photocurrent (I ph ), and subsequently to the resulting membrane potential (V m ). Using the PCE12:ITIC-based solar cell platform, we experimentally demonstrate polarization-dependent modulation of photovoltage and photocurrent, and directly correlate these effects with intracellular calcium dynamics. Calcium imaging of hippocampal neurons revealed robust, stimulus-locked ΔF/F₀ transients on PCE12:ITIC substrates under light stimulation, in contrast to minimal responses on control ITO films, confirming that polarization-modulated excitonic processes drive physiologically relevant changes in neuronal signaling. Moreover, we highlight how dipole–membrane coupling provides a conceptual and functional link between neuromodulation and quantum logic systems, especially when realized through nanocrystal-based harmonic oscillators. InP-ZnO nanoclusters exhibit selective responses to left circularly polarized (LCP) light, offering pixel-wise selectivity for color-encoded retinal stimulation. Bioinspired anisotropic quantum dot arrays, modeled after polarization-sensitive ommatidia in bee eyes, enable spatially selective neuromodulation and programmable bio-optoelectronic interfaces.